Wspomaganie żywieniowe pacjentów geriatrycznych z postępującą sarkopenią = Supporting nutrition in geriatric patients with progressive sarcopenia - Nowak, Karina; Porażyńska, Daria; Ciesielska, Natalia; Stemplowski, Wojciech; Sokolowski, Remigiusz; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Nowak Karina, Porażyńska Daria, Ciesielska Natalia, Stemplowski Wojciech, Sokolowski Remigiusz, Zukow Walery. Wspomaganie żywieniowe pacjentów geriatrycznych z postępującą sarkopenią = Supporting nutrition in geriatric patients with progressive sarcopenia. Journal of Education, Health and Sport. 2015;5(7):216-225. ISSN 2391-8306. DOI 10.5281/zenodo.19940 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A216-225 https://pbn.nauka.gov.pl/works/583641 http://dx.doi.org/10.5281/zenodo.19940 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. Wspomaganie żywieniowe pacjentów geriatrycznych z postępującą sarkopenią Supporting nutrition in geriatric patients with progressive sarcopenia Karina Nowak1, Daria Porażyńska1, Natalia Ciesielska1, Wojciech Stemplowski1, Remigiusz Sokolowski1, Walery Zukow2 1Katedra i Klinika Geriatrii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp. Sarkopenia to postępująca wraz z wiekiem utrata tkanki mięśniowej która przyczynia się do pogorszenia funkcji mięśni zwiększając ryzyko upadków, złamań kości oraz nasilenia niepełnosprawności. W świetle dzisiejszych doniesień naukowych żywienie może być istotnym elementem wspomagającym u pacjentów z postępującą sarkopenią. Cel. Przedstawienie aktualnych doniesień dotyczących wspomagania żywieniowego w przypadku postępującej sarkopenii mięśniowej. Materiał i metody. Posługując się słowami kluczowymi: sarkopenia (sarcopenia), żywienie w sarkopenii (nutrition in sarcopenia), witamina D (vitamin D), osoby starsze (elderly people), dieta białkowa (protein diet/ intake) , starzenie (ageing), epidemiologia (epidemiology), stan odżywienia (nutrition status), otyłość sarkopeniczna (sarcopenic obesity), antyoksydanty (antioxidant), dieta niskokaloryczna (low energy diet), mięsnie szkieletowe (skeletal muscles), przeszukano elektroniczne polskie oraz zagraniczne pełnotekstowe bazy bibliograficzne: Polska Bibliografia Lekarska, EBSCO host Web, Wiley Online Library, Springer Ling, Science Direct oraz Medline. Ostatecznie przeanalizowano 48 publikacji dotyczących sarkopenii z ostatnich 18 lat. Wyniki. Przegląd literatury ukazuje, że stan odżywiania organizmu tj. niedożywienie oraz otyłość istotnie może wpłynąć na postepowanie sarkopenii mięśniowej. Wśród naukowców, odnotowano duże zainteresowanie dietą wysokobiałkową, restrykcyjną oraz dietą wzbogaconą o suplementacje antyoksydantów oraz witaminę D. Wnioski. Zaobserwowano, że aktualnie brakuje badań, które jednoznacznie potwierdzą skuteczność stosowanego wspomagania żywieniowego w sarkopenii mięśniowej. Dieta restrykcyjna stosowana w leczeniu i zapobieganiu sarkopenii prócz tego, iż nie może doprowadzać do niedożywienia musi zawierać prawidłowe ilości wszystkich składników odżywczych i witamin. Obniża się wtedy produkcja wolnych rodników, stymuluje biogeneza a także mechanizmy obronne mitochondriów w mięśniach oraz można tym samym zapobiegać apoptozie rabdomiocytów. Istotne ograniczenia dziennego dowozu kalorii są jednak często źle tolerowane przez starsze osoby o prawidłowym wskaźniku masy ciała a badania nad wpływem diety restrykcyjnej na postęp zaniku mięśni i uszkodzeń DNA nadal trwają. Znaczenie w diecie osób z postępującą sarkopenią ma także prawidłowe stężenie witaminy D w surowicy. Istnieją badania wskazujące na to, że niskie stężenie 25-OHD i wysokie stężenie parathormonu (PTH ≥4.0 pmol / litr) zwiększają ryzyko rozwoju sarkopenii u starszych mężczyzn i kobiet [42]. Słowa kluczowe: sarkopenia, dieta, osoby starsze. Abstract Introduction. Sarcopenia is progressing with age, loss of muscle tissue that contributes to the deterioration of muscle function by increasing the risk of falls, fractures and severity of disability. In the light of today's scientific reports nutrition may be an important element supporting patients with progressive sarcopenia. Purpose. Presentation of the recent reports of nutritional support for progressive muscle sarcopenia. Materials and methods. Using the keywords: sarcopenia (sarcopenia), nutrition in sarcopenia (nutrition in sarcopenia), vitamin D (vitamin D), the elderly (elderly people), protein diet (protein diets / intake), aging (aging), epidemiology (epidemiology ), nutritional status (nutrition status), obesity sarcopenic (sarcopenic obesity), antioxidants (antioxidant), low-calorie diet (low energy diet), skeletal muscle (skeletal muscles), searched electronic full-text Polish and foreign bibliographic databases: Polish Medical Bibliography, EBSCO Web host, Wiley Online Library, Springer Ling, Science Direct, and Medline. Finally, they analyzed 48 publications on sarcopenia over the past 18 years. Results. The literature review shows that the nutritional status of the organism, ie. Malnutrition and obesity can significantly affect the outcome sarcopenia muscle. Among scientists, there has been great interest in high protein diet, a restrictive and supplemental diet enriched with antioxidants and vitamin D. Conclusions. It was observed that currently lack research that clearly confirm the effectiveness of the nutritional support in muscle sarcopenia. Restrictive diet used in the treatment and prevention of sarcopenia except that it may not lead to malnutrition must contain the proper amounts of all nutrients and vitamins. Then descends free radical production, stimulates biogenesis and we defense mechanisms of mitochondria in muscle and may thus prevent apoptosis rabdomyocytes. Significant limitations calories daily commutation, however, are often not well tolerated by older people with normal body mass index and research on the effects of diet restriction on muscle atrophy progression and DNA damage are still ongoing. The importance in the diet of people with progressive sarcopenia also has the correct amount of vitamin D in serum. There are studies indicating that low levels of 25-OHD and high levels of parathyroid hormone (PTH ≥4.0 pmol / L) increase the risk of development of sarcopenia in older men and women [42]. Keywords: sarcopenia, diet, older people.